Localisation and characterisation of substance P binding to human synovial tissue in rheumatoid arthritis. Issue 3 (March 1992) - Walsh, D A; Mapp, P I; Wharton, J; Rutherford, R A; Kidd, B L; Revell, P A; Blake, D R; Polak, J M
Abstract : The neuropeptide substance P is found in perivascular and free unmyelinated nerve fibres in human synovial tissue. Quantitative receptor autoradiography was used to show specific, high affinity (Kd = 0.75 (0.21), nmol/l (mean (standard error of the mean)), low capacity (Bmax = 27.8 (7.9) amol/mm2) binding sites for substance P Bolton Hunter-labelled with iodine-125 localised to vascular endothelial cells in human synovial tissue. The binding could be saturated, was reversible, and was dependent on the magnesium concentration. Unlabelled substance P and neurokinin A competitively inhibited specific binding with 50% inhibition at concentrations of 1.25 (0.21) and 175 (29) nmol/l respectively. Neurokinin B (mumol/l) and calcitonin gene related peptide (1 mumol/l) did not inhibit binding. These binding sites show characteristics of the neurokinin 1 tachykinin receptor subtype. This provides further evidence that substance P may play a part in the vascular control of human synovium and may influence inflammatory processes in joints.